Performance of fly ash concrete with ferronickel slag fine aggregate against alkali-silica reaction and chloride diffusion. (January 2021) - Nguyen, Quang Dieu; Castel, Arnaud; Kim, Taehwan; Khan, Mohammad S.H.
Abstract: Ferronickel slag (FNS) is an industrial by-product of ferronickel alloy production at a high temperature which can be a promising potential to be used as fine aggregate to produce more sustainable concrete. In this study, the performance of concrete containing ferronickel slag sand and fly ash relating to alkali-silica reaction (ASR) and chloride contamination was investigated. ASR-induced expansion, chloride diffusion resistance, and chloride binding capacity of FNS concrete were determined through concrete prism tests (CPT), accelerated diffusion test, and bulk diffusion test. Thermogravimetric analysis (TGA) was conducted to measure the amount of Portlandite and Friedel's salt in concrete. Concrete with 50 wt% FNS sand as fine natural aggregate replacement and 25 wt% of cement replacement by fly ash showed a remarkable potential to be used not only as a low-carbon concrete with comparable mechanical properties to conventional concrete but also with a better performance against ASR and chloride contamination.